2019
DOI: 10.1039/c9ra07109a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh permeance of a chemical cross-linked graphene oxide nanofiltration membrane enhanced by cation–π interaction

Abstract: Chemical cross-linking together with magnesium ions, potentially promoting reasonable cross-linking and improving the water channels of membrane in terms of flatness and surface with low mass transfer resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 31 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…As shown in Figure 4c,d the proportion of oxygen-containing functional groups can be obtained according to C1s curve-fitting peak analysis. Four peaks at 284.6 eV, 286.7 eV, 287.8 eV and 288.9 eV correspond to C-C/C=C, C-O/C-O-C, C=O and O-C=O, respectively [3,19,32,33]. It can be observed that the amount of hydroxyl/epoxy in GO is lower than that in HGO, which is consistent with the FTIR results.…”
Section: Characterization Resultssupporting
confidence: 86%
“…As shown in Figure 4c,d the proportion of oxygen-containing functional groups can be obtained according to C1s curve-fitting peak analysis. Four peaks at 284.6 eV, 286.7 eV, 287.8 eV and 288.9 eV correspond to C-C/C=C, C-O/C-O-C, C=O and O-C=O, respectively [3,19,32,33]. It can be observed that the amount of hydroxyl/epoxy in GO is lower than that in HGO, which is consistent with the FTIR results.…”
Section: Characterization Resultssupporting
confidence: 86%
“…The important noncovalent cation-π interaction between cations and the delocalized aromatic graphene domains distributed in rGO 32 are supposed to be at the origin of the change in the surface charges of rGO 33 . In the case of Mg 2+ , the higher charge density as a divalent cation 34 , 35 explains the higher adsorption energy induced by cation-π interaction versus Li + 35 , 36 . Therefore, the enrichment of Mg 2+ onto the rGO surface is expected to effectively screen the surface charge and makes the surface zeta potential less negative than Li + .…”
Section: Resultsmentioning
confidence: 99%
“…3B). [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Furthermore, glutaraldehyde 67 and 1-allyl-3-vinylimidazolium chloride 68 have also been utilized as cross-linking agents to improve the stability of the GO membrane in water. Although covalent cross-linking can endow the GO membranes with enough stability in water, the excessive cross-linking will disturb and block water transport within the GO nanochannels, leading to the decrease of the water flux of the membrane.…”
Section: Strategies For Improving the Stability Of Go Membranes In Watermentioning
confidence: 99%